Research Timeline: Form-focused instruction and second language acquisition. (7th December 2015) - Nassaji, Hossein
Abstract : This article provides a timeline of research on form-focused instruction (FFI). Over the past 40 years, research on the role of instruction has undergone many changes. Much of the early research concentrated on determining whether formal instruction makes any difference in the development of learner language. This question was motivated in part by a theoretical discussion in the field of cognitive psychology over the role of explicit versus implicit learning, on the one hand, and a debate in the field of second language acquisition (SLA) over the role of naturalistic exposure versus formal instruction, on the other. In the early 1980s, for example, based on the notion that the processes involved in second language (L2) learning are similar to those in first language (L1) learning, Krashen (e.g., Krashen1981, 1982, 1985 ) made a distinction between learning and acquisition and claimed that an L2 should be acquired through natural exposure not learned through formal instruction. Thus, he claimed that FFI has little beneficial effect on language acquisition. This position, which has also been known as a 'zero position' on instruction, was also taken by a number of other researchers who argued that L1 and L2 learning follow similar processes and that what L2 learners need in order to acquire a second language is naturalistic exposure to meaning-focused communication rather than formal instruction (Dulay & Burt1974 ; Felix1981 ; Prabhu1987 ; Schwartz1993 ; Zobl1995 ).